Evaluation of selected legumes for sustainable weed ecology/soil fertility/livestock management interactions in crop-livestock systems of the moist savannah of Nigeria - Owoeye, Lawrence Gbadebo (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2004.